2013
DOI: 10.1523/jneurosci.5689-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Otoferlin Couples to Clathrin-Mediated Endocytosis in Mature Cochlear Inner Hair Cells

Abstract: The encoding of auditory information with indefatigable precision requires efficient resupply of vesicles at inner hair cell (IHC) ribbon synapses. Otoferlin, a transmembrane protein responsible for deafness in DFNB9 families, has been postulated to act as a calcium sensor for exocytosis as well as to be involved in rapid vesicle replenishment of IHCs. However, the molecular basis of vesicle recycling in IHCs is largely unknown. In the present study, we used high-resolution liquid chromatography coupled with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(120 citation statements)
references
References 72 publications
(123 reference statements)
3
116
0
1
Order By: Relevance
“…3G). This subcellular distribution is similar to observations made on mouse hair cells (20,23,37). Probing 120-h wild-type zebrafish with the FM1-43 dye (Fig.…”
Section: Zebrafish Have Two Copies Of Otoferlinsupporting
confidence: 86%
See 1 more Smart Citation
“…3G). This subcellular distribution is similar to observations made on mouse hair cells (20,23,37). Probing 120-h wild-type zebrafish with the FM1-43 dye (Fig.…”
Section: Zebrafish Have Two Copies Of Otoferlinsupporting
confidence: 86%
“…Otoferlin is a six-C2 domain transmembrane protein expressed in inner, outer, and vestibular hair cells, as well as restricted regions of the brain (13-16). In humans, missense mutations in otoferlin have been linked to hearing loss (17,18), and biochemical studies have determined that otoferlin binds calcium and lipids (12,19), as well as membrane trafficking proteins (12,(20)(21)(22)(23). Further, in vitro assays have demonstrated that otoferlin accelerates SNARE-mediated membrane fusion (12).…”
Section: Sensory Hair Cells Convert Mechanical Motion Into Chemical Smentioning
confidence: 99%
“…Otoferlin has recently been found to interact with AP-2 and myosin VI, two proteins involved in clathrin-mediated endocytosis (Duncker et al, 2013), which is essential to synaptic vesicle replenishment. On these grounds a further role for otoferlin has been suggested: it could be involved in coupling exocytosis and endocytosis in IHCs, thus providing the basis for sustained release at the ribbon synapse.…”
Section: Otof Gene Mutations Results In Pre-synaptic Auditory Neuropathymentioning
confidence: 99%
“…4). Otoferlin could prime synaptic vesicles for fusion 19 , potentially via promoting the for mation of short tethers between synaptic vesicles and the membrane of the active zone, as suggested by elec tron tomography 29 , and/or it could facilitate the clear ance of previously exocytosed material from the release site via interaction with endocytic proteins 18,63 . Missense mutations might affect these processes by lower ing the otoferlin levels or by impairing its interactions with other proteins.…”
Section: Genetic Auditory Synaptopathiesmentioning
confidence: 99%